Pengaruh Metode Praktikum Terhadap Minat Dan Hasil Belajar Siswa Pada Mata Pelajaran Fikih (Studi Pada Siswa Kelas X MAN 1 Kota Bengkulu) - Sherly Lisfitriani; Irwan Satria; Pasmah Chandra (GHAITSA : Islamic Education Journal, 2025)
In the learning process, the use of varied methods is one of the important factors for the success of a learning process. This study aims to analyze: First, the effect of practical methods on students' interest in learning Islamic jurisprudence. Second, to determine the effect of practical methods on students' learning outcomes in Islamic jurisprudence. Third, to determine the effect of practical methods on students' interest and learning outcomes in Islamic jurisprudence. This research was conducted at MAN 1 Kota Bengkulu using a quantitative experimental method. The research sample consisted of 68 tenth-grade students. The research instruments used questionnaires and learning outcome tests (post-test). Data analysis techniques were carried out using the T-test and MANOVA hypothesis tests. The results of the study show: First, there is a significant effect between practical methods and students' interest in learning Islamic jurisprudence. Second, there is a significant effect between practical methods and students' learning outcomes in Islamic jurisprudence. Third, there is a significant effect between practical methods on students' interest and learning outcomes in Islamic jurisprudence